The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1101/2023.11.17.567518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosomal Integrons are Genetically and Functionally Isolated Units of Genomes

Paula Blanco,
Filipa Trig da Roza,
Laura Toribio-Celestino
et al.

Abstract: Integrons are genetic elements that increase the evolvability of bacteria by capturing new genes and stockpiling them in arrays. Sedentary chromosomal integrons (SCIs), can be massive and highly stabilized structures encoding hundreds of genes, whose function remains generally unknown. SCIs have co-evolved with the host for aeons and are highly intertwined with their physiology from a mechanistic point of view. But, paradoxically, other aspects, like their variable content and location within the genome, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…An extreme case of this is shown by Darracq et al in a back-to-back paper in this issue, where they describe the presence of PICs in the Superintegron of Vibrio cholerae. Indeed, in a recent work we have shown that the Superintegron is carried at no measurable cost 59 . Additionally, their findings proves that chromosomal integrons are virtually infinite repositories of PICs from where they can be recollected by mobile integrons.…”
Section: Discussionmentioning
confidence: 99%
“…An extreme case of this is shown by Darracq et al in a back-to-back paper in this issue, where they describe the presence of PICs in the Superintegron of Vibrio cholerae. Indeed, in a recent work we have shown that the Superintegron is carried at no measurable cost 59 . Additionally, their findings proves that chromosomal integrons are virtually infinite repositories of PICs from where they can be recollected by mobile integrons.…”
Section: Discussionmentioning
confidence: 99%